Aggregate Industry Behaviour in a Monopolistic Competition Model with Heterogeneous Firms - Erling Holmøy (Statistics Norway, Research Department, 2003)
The paper analyses how a tractable representation of productivity heterogeneity among firms modifies the standard Dixit-Stiglitz (DS) model of monopolistic competition. The properties of the asymmetric model are explored by comparative statics analysis. The equilibrium adjustments of industry aggregates, such as the number of firms, output and the productivity of variable inputs are compared with the corresponding adjustments in the symmetric model. The analysis thereby clarifies when and why the standard DS model may provide a misleading picture of the aggregate industry behaviour. A by-product of the paper is to demonstrate that a more realistic description of a basic aspect of technology heterogeneity can be taken into account at a relatively low cost in terms of reduced tractability.
Keywords: L11; L13; L16; 330; Monopolistic competition; productivity heterogeneity; aggregation